Design Support Education Innovation on Digital Era - Yuliati, Yuliati; Lelawati, Irma (Universitas Muhammadiyah Surakarta, 2019)
Environmental education provides opportunity to joyful learning with integrate ofeducational contents and entertainment activities. Understanding environmentaleducation is greatly helped by the existence of new technology waves. Fast-movinginnovation of new technology waves is digitalization. That is called the fourth industrial revolution. One of them is Artificial Intelligence (AI) technology. AI knowledge and innovation systems have made promising help students to realize that it can be increase respect for oneself and others, express feelings and opinions, and build logical thinking about science, mathematics, computer, etc. This paper build based on elementary school student experiment in Surakarta about how to understand digital technology based on AI and environment. This study is ethnography and qualitative research. As a data collection instrument, the study uses an assesment consisting of observation and questionnaire. This paper reports on 1) creating ideas resources, 2) learning educational contents and entertainment activities, 3) understanding feedback interaction, and 4) evaluating the challenges. The end of this paper shows that AI is very helpful in environmental education for elementary school students.